ANXIETY IN QURAN (Thematic Study on Quran) - Muhdar Muhdar (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
Generally, every one ever felt an anxiety, the anxiety was normal experienced by people. However, might not let the heart and mind in anxiety, even less anxieted anything not yet happen. In addition, if talked about anxiety could not free from counseling.Therefore, than viewed in this skripsi are how the describe in Quran about anxiety trhougt the verses related conseling? and how the interpretation of the interpretator about these verses?Research method design in skripsi was maudhu`i, in which the research only discusses one topic of discussion and then collected the verses that have meaning, theme or content of the same relating to anxiety. Then the researcher arranged chronogically the verses based of Asbabun Nuzul, where the research would make systematically.The research result showed that the anxiety could same with khauf, because same was a part of fair or fair emotion of unpleasant or the fair of the situation not yet happen. Looked the interpretation from the interpretator and psychology expert, could know than the anxiety had overcome, expecially the Quran was very prompt with surrender of Allah Swt.From the conclusion was gotten than anxiety disease can lost, in opinion of the researcher than overcome anxiety was heart grateful. Grateful of heart would calm feeling because everything is handed to God.